The ambiguous descriptions of Japanese morphography and agglutination: a critical analysis of relations between graphemics and morphology in the Japanese language - Nowak, Radosław (Silva Iaponicarum, 2026)
In a morphographic script, graphemes represent morphemes; in an agglutinative language, monosemous morphemes attach onto lexical ones to convey grammatical meanings. Although these definitions are generally accepted, the former lacks the nuance needed to accurately describe grapheme–morpheme relations within the Japanese writing system, and the latter is often overlooked in accounts of Japanese morphosyntax. This paper identifies these mismatches and draws connections between Japanese morphography and descriptions of Japanese morphology. Sections 1 and 2 examine how kanji characters may correspond to exactly one morpheme, more than one morpheme, or less than one morpheme; and how different scripts represent different morpheme types. Section 3 outlines logical and terminological inconsistencies in Japanese grammars. Section 4 links features of the writing system to the ways Japanese morphosyntax is analyzed. The paper concludes that treating certain inflectional morphemes as lexical items may stem from the “division of labor” between morphographic kanji and phonographic kana.